Development of an agricultural vehicle levelling system based on rapid active levelling. (October 2019) - Wang, Zhuangzhuang; Yang, Jie; Liu, Pingyi; Long, Xinjiani; Li, Haitao; Wei, Wenjun
Abstract : Agricultural vehicles are typically unable to maintain a level position and therefore unable to guarantee the quality of work when operated on uneven terrain. Current levelling methods mostly depend on adjustments that are passive or delayed with adjustment taking place after the bodywork has tilted. The objective of this research was to propose a rapid active levelling method, in which levelling starts as soon as the vehicle platform begins to tilt, thus actively preventing or reducing vehicle body inclination. The design relies on a ground detection device installed in front of each wheel of the four-wheels of the agricultural vehicle, which senses ground information ahead of the vehicle in its normal direction of motion. This information combined with the agricultural vehicle's driving condition is then used to determine the instantaneous adjustments necessary for moving the levelling actuator ensuring that the work platform remains level. The principle of coordinated deformation of four-wheel vehicle chassis suspension was studied by using virtual prototyping technology. By using the coordinate transformation method, a calculation formula between the platform adjustment angle and variations in pitch or roll angle was derived, as well as the required formula relating the displacement of the adjustment device and the platform adjustment angle. Experiments showed that the designed levelling system based on the rapid active levelling method could maintain the pitch angle and roll angle of the platform within less than ±0.5° for more than 80% of the duration of the tests. Highlights: Most of the current levelling methods are lag or passive methods. Rapid active levelling is where levelling starts as soon as tilting is detected. 4-wheel drive suspension was described using suspension coordinated deformation. Vehicle levelling based on rapid active levelling method showed high precision.